The solution to 6.6 - 1/3 without using a calculator is 94/15.
Given is a subtraction expression 6.6 - 1/3, we need to solve it,
To solve 6.6 - 1/3, we can convert the decimal number 6.6 into an improper fraction.
Convert the decimal 6.6 to an improper fraction.
We can rewrite 6.6 as 6 + 0.6. Since there are 6 whole units and 6 tenths, we can express it as:
6.6 = 6 + 6/10
6.6 = 6 + 3/5
Now, subtract 1/3 from 6 + 3/5.
To subtract fractions, we need to find a common denominator. In this case, the common denominator is 15, which is the least common multiple (LCM) of 3 and 5.
6 + 3/5 - 1/3 can be rewritten with the common denominator of 15:
(6 x 15)/15 + (3 x 3)/15 - (1 x 5)/15
Simplifying the numerator, we get:
90/15 + 9/15 - 5/15
Now, combine the numerators:
(90 + 9 - 5)/15
Simplifying further:
94/15
Therefore, the solution to 6.6 - 1/3 is 94/15.
Learn more about Subtraction click;
#SPJ6
Answer:
1.6%
Step-by-step explanation:
The real GDP is given by the nominal GDP divided by the GDP deflator, the real GDP for year 1 and year 2, respectively, were:
The percentage change in GDP is:
Between year 1 and year 2, real GDP rose by 1.6%.
51.2 km
35.7 km
113.2 km
You will need to multiply 15.5 by 2.3. Keep in mind that this only works because the scale is 1cm but if it was say.... 3.4cm:15.5 you wouldn't be able to use that method. Yeah so the answer is 35.65 which rounds up to →35.7← because the second decimal place is five
Answer:
35.7km
Step-by-step explanation:
Answer:
lhs = (5+2√3)/(7+4√3)
= [(5+2√3)(7-4√3)]/[(7-4√3)(7+4√3)]
=[35-20√3+14√3-24]/[7²-(4√3)²]
=[11-6√3]/[49-48]
=11-6√3
therefore
11-6√3 = a+b√3
compare both sides
a= 11, b= -6
Step-by-step explanation:
Hope this answer helps you :)
Have a great day
Mark brainliest
Answer:
a = 11, b = 6
Step-by-step explanation:
Given
Rationalise the denominator by multiplying numerator/ denominator by the conjugate of the denominator.
The conjugate of 7 + 4 is 7 - 4
= ← expand numerator/ denominator using FOIL
=
=
= 11 - 6
with a = 11 and b = 6